English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(y/x - x/y) / (x-y)

2007-04-27 19:38:11 · 5 answers · asked by Vokalskilz 1 in Science & Mathematics Mathematics

5 answers

= (y² - x² / xy) / (x - y)
= (y - x).(y + x) / (xy)(x - y)
= - (x - y).(x + y) / (xy)(x - y)
= - (x + y) / xy

2007-04-27 20:53:57 · answer #1 · answered by Como 7 · 0 0

(y/x-x/y)/(x-y)
={(y^2-x^2)/xy}/(x-y)
={(y+x)(y-x)/xy}/(x-y)
={-(x+y)(x-y)/xy}/(x-y)
= - (x+y)/xy
The answer can be written as
-(x/xy+y/xy
= -1/y+1/x
=1/x -1/y

2007-04-28 04:54:19 · answer #2 · answered by alpha 7 · 0 0

y^2-x^2/xy(x-y)
-(x+y)(x-y)/xy(x-y
=-(x+y)/xy

2007-04-28 02:41:55 · answer #3 · answered by raj 7 · 1 0

[y^2-x^2/xy]/[x-y]
[y-x][y+x]/xy[x-y]
[x+y]/xy

2007-04-28 04:03:43 · answer #4 · answered by Kuan T 2 · 0 0

(y/x-x/y)/(x-y)
={(y^2-x^2)/xy}/(x-y)
=(y^2-x^2)/(x-y)(xy)
=(y+x)(y-x)/(x-y)xy
=(-x-y)/xy

2007-04-28 03:07:14 · answer #5 · answered by Harsh 2 · 0 0

fedest.com, questions and answers